PESIN conjugates for multimodal imaging: can multimerization compensate charge influences on cell binding properties? : a case study - Hübner, Ralph; Paretzki, Alexa; Kiedrowski, Valeska von; Maspero, Marco; Cheng, Xia; Davarci, Güllü; Braun, Diana; Damerow, Helen; Judmann, Benedikt; Filippou, Vasileios; Dallanoce, Clelia; Schirrmacher, Ralf; et al. (Pharmaceuticals, 2021)
Recently, anionic charges were found to negatively influence the in vitro gastrin-releasing peptide receptor (GRPR) binding parameters of dually radioisotope and fluorescent dye labeled GRPR-specific peptide dimers. From this, the question arose if this adverse impact on in vitro GRP receptor affinities could be mitigated by a higher valency of peptide multimerization. For this purpose, we designed two different hybrid multimodal imaging units (MIUs), comprising either one or two click chemistry-compatible functional groups and reacted them with PESIN (PEG3-BBN7-14, PEG = polyethylene glycol) dimers to obtain a dually labeled peptide homodimer or homotetramer. Using this approach, other dually labeled peptide monomers, dimers, and tetramers can also be obtained, and the chelator and fluorescent dye can be adapted to specific requirements. The MIUs, as well as their peptidic conjugates, were evaluated in terms of their photophysical properties, radiolabeling efficiency with 68Ga and 64Cu, hydrophilicity, and achievable GRP receptor affinities. Here, the hydrophilicity and the GRP receptor binding affinities were found to be especially strongly influenced by the number of negative charges and peptide copies, showing logD (1-octanol-water-distribution coefficient) and IC50 (half maximal inhibitory concentration) values of −2.2 ± 0.1 and 59.1 ± 1.5 nM for the homodimer, and −1.9 ± 0.1 and 99.8 ± 3.2 nM for the homotetramer, respectively. From the obtained data, it can be concluded that the adverse influence of negatively charged building blocks on the in vitro GRP receptor binding properties of dually labeled PESIN multimers can, at least partly, be compensated for by the number of introduced peptide binding motives and the used molecular design.